Efektivitas Dimensi Electronic Word Of Mouth (E-WOM) Di Instagram Terhadap Keputusan Berkunjung Wisatawan - Sri Marini; Lu’luwatin Rosdiana Aprilia; Idham Sakti Wibawa (Politeknik Piksi Ganesha Indonesia, 2022)
SSocial media has a role in an e-wom. Instagram is one of the social media with the most users today. The purpose of this study is to determine the effectiveness of the dimensions of e-wom (intensity, valence of opinion, content) on Instagram on the decision to visit The Great Asia Afrika (TGAA) Lembang tourists. The method used in this study is verification and descriptive research methods. Population is visitors and sample determination uses a purposive tehnique with the criteria who have visited and followed TGAA's Instagram. Statistical method use multiple linear regression. The results of the study showed that the valence of opinion dimension was not significant on the decision of tourist visit. Simultaneously, the dimensions of E-WOM have a significant effect 55.60% and its can be interpreted that the effect of the E-WOM dimension of Instagram is effective as a social media platform on the decision to visit TGAA tourists.